Study of the Purchasing Intention of Tourists for Guizhou In-tangible Cultural Heritage Batik Products - Yaguang Jin; Jacky Mong Kwan Watt (International Forum of Researchers and Lecturers, 2025)
This study explores the influence of live streaming mode on the purchase intention of tropical fruits among consumers in Henan, China, in the context of the rapid growth of e-commerce. Live streaming has emerged as a dynamic and interactive platform that enables real-time engagement between sellers and buyers, offering visual product demonstrations and instant feedback opportunities. The research focuses on three critical factors affecting purchase intention: perceived trust, perceived value, and perceived risk. A quantitative research design was employed, collecting data from 392 participants through structured questionnaires. The analysis indicates that interactive communication, transparent information sharing, and authentic presentations during live streaming significantly enhance perceived trust and perceived value. Higher perceived trust fosters a stronger sense of reliability toward sellers, while increased perceived value motivates consumers by highlighting product quality, freshness, and fair pricing. Furthermore, effective live streaming strategies can substantially reduce perceived risks related to product authenticity, quality uncertainty, and transaction security, creating a more favorable purchase environment. The results suggest that the integration of engaging storytelling, professional product showcasing, and active audience interaction serves as a catalyst for influencing consumer attitudes and behaviors toward purchasing tropical fruits. This study enriches the existing literature on live streaming commerce by highlighting its psychological and behavioral impacts on consumer decision-making. In practical terms, the findings offer actionable insights for marketers and fruit sellers, emphasizing the importance of building trust, delivering genuine product experiences, and minimizing risks to maximize purchase intentions. These strategies are particularly relevant for agricultural e-commerce in Henan, where live streaming can bridge the gap between rural producers and urban consumers. Overall, this research provides both theoretical contributions to the study of digital co sumer behavior and practical guidance for optimizing live streaming as a competitive marketing tool in the fresh produce industry.